When a risky prospect is valued more than its best possible outcome - Andreas C. Drichoutis; Rodolfo M. Nayga; Jayson L. Lusk; Panagiotis Lazaridis (Judgment and Decision Making, 2012)
In this paper, we document a violation of normative and descriptive models of decision making under risk. In contrast to uncertainty effects found by Gneezy, List and Wu (2006), some subjects in our experiments valued lotteries more than the best possible outcome. We show that the overbidding effect is more strongly related to individuals’ competitiveness traits than comprehension of the lottery’s payoff mechanism.